EVOLUSI MIKROSTRUKTUR DARI KERAMIK PADUAN SILIKA (SiO2) DAN ALUMINA (Al2O3) - L. Lestari; R. Riwasa; P.E. Susilowati; I.N. Sudiana (Universitas Halu Oleo, 2017)
The study on the effect of sintering temperature on the microstructure of ceramic to microstructure of silica (SiO2 and alumina (Al2O3) composite was successfully performed. The microstructure from SEM photos of samples after sintering as well as their crystallinity were studied. Sintering were performed by using electric furnace (conventional) and 2.45 GHz microwave. The crystallinity was determined by using X-Ray Diffraction (XRD). SEM photos shows that with the increasing of sintering temperature, the porosity of samples decreased quickly, the density and hardness also increased. There are differences of their properties between conventional and microwaved sintered samples at same sintering temperature. XRD graphs shows that the crystallinity of samples on sintering by using microwaves higher than that of conventional heating.